The barber of Seville - Sterbini, Cesare, 1784-1831 (Opera Journeys, 2005)
A comprehensive guide to Rossini's THE BARBER OF SEVILLE, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 35 music highlight examples.
Libretto by Cesare Sterbini.
Based on: Le Barbier de Séville / Pierre Augustin Caron de Beaumarchais.
Keywords: Rossini, Gioacchino, -- 1792-1868. -- Barbiere di Siviglia.; Barbiere di Siviglia (Rossini, Gioacchino); Operas -- Librettos.; Opéras -- Livrets.; MUSIC -- Genres & Styles -- Opera.; Operas -- Librettos